Quadratic dependence on temperature of Cs 0-0 hyperfine resonance frequency in single Ne buffer gas microfabricated vapour cell - Miletic, Danijela; Dziuban, Piotr; Boudot, Rodolphe; Hasegawa, M.; Chutani, R.K.; Mileti, Gaetano; Giordano, Vincent; Gorecki, Christophe (My University, 2010)
Presented is the observation of a quadratic temperature dependence of the Cs 0-0 ground state hyperfine resonance frequency in a single Neon (Ne) buffer gas vapour microcell. The inversion temperature, expected to be theoretically independent of the buffer gas pressure, is measured to be about 80-C for two different samples. A proposal to develop chip scale atomic clocks with improved long-term frequency stability, simpler configuration (a single buffer gas instead of a buffer gas mixture) and then relaxed constraints on pressure accuracy during the cell filling procedure is presented.